Cataloguer, indexer, encoder - Tiziana Nicoletta Beltrame; Christine Jungen (Revue d'anthropologie des connaissances)
The article looks at the production and manipulation of accumulation management systems. It enters into the infrastructures designed to put in order and make accessible the accumulation of knowledge through their materiality and questions the productions, configurations and manipulations of information, data and inscriptions. The problems and issues at stake in these systems lie at the crossroads of several fields of reflection, including taxonomy, data and standards production, the ecology of information infrastructures and cooperation between communities of practice. The information and communication technologies on which the information society is based are based on equipment that amplifies the dissemination, storage and organization of heterogeneous aggregates. These systems of knowledge production are invisible but highly political. The perspective adopted inherits as much from the anthropology of material cultures as from the attention paid to ontologies and modes of human and non-human presence. The aim is to situate digital techniques for storing knowledge into a set of document management practices, including listing, inventory or catalogue, card or print. These digital technologies are endowed with a materiality whose properties and specificities must be explored. They constitute places for exercising control policies at the same time as data constitute environments with a specific texture that act in return on the normative structures in which they are inscribed.